Profesiones de servicio y digitalización: implicaciones y sugerencias para la concepción de procesos de formación - Deli Salini; Juana Sarmiento Jaramillo; Annie Goudeaux; Germain Poizat (Universidade do Porto, 2018)
In the services sector professions, digitalization is transforming the individual and collective activity and the relationship with the users. Though not exclusively, this aspect is particularly visible when digitalization refers to the management of the user's information. This contribution explores the implications of the information's digitalization (of clients, patients). It is based on two preliminary studies carried out in Switzerland, about the practice of nurses and bailiffs. The studies followed the view of educational anthropotechnology and showed that the introduction of technical digital objects (TDO) leads to profound transformations in work. These are discussed according to three lines of thought: a) the relationship between the wide circulation of the TDO and the organizational evolution of services sector professions, b) the inherent complexity in the transformation of communication's modalities and media, and c) the need to propose educational interventions addressing digital practices preparation or reparation.